FEATURES AND PROBLEMS OF LITERARY TRANSLATION - Komila Hasanovna Sayitova; Uktamov Mukhammadyusuf (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Literary translation has an important place in modern translation theory. Literary translation is a special area of translation activity, which is a written translation of works of art from one language into another. The main difficulty of literary translation lies not only in the transfer of meaning, but in the transfer of the unique style of the author of the work, his aesthetics, the richness of the use of linguistic means, as well as the humor, atmosphere, character and mood hidden in the text, therefore literary translation trenches not only upon linguistics and philology, it skirts on art.